Differences in goalkeepers` performance indicators at three consecutive Men`s European Championships held in 2002, 2004 and 2006 - Pori, P.; Mohorie, U.; Tomazini, D.; Sibila, M. (World Congress of Performance Analysis of Sport VIII, 2008)
We may derive from our results that, in spite of the statistically significant rise in the overall average number of shots, the average number of shots from 9 m and the wing position in the last two EChs, the number of goalkeepers` saves remained at the same level (ECh`02 - 31.69%; ECh`04 - 32.6%; ECh`06 - 32.0%). So we can conclude that the efficiency of saving reached its peak some years ago and in the last few years it slightly dropped. We may also speculate that improvements in the skills of shooters and goalkeepers developed simultaneously. Shooters are trying to find new ways of shooting and especially in the last few years they have being shooting more freely. As a consequence, goalkeepers seek to adapt their strategies to this kind of shooters. Therefore, we can conclude that the analysis of the statistical data does not really corroborate the findings of the qualitative analysis of goalkeepers` performances at the ECh 2006 (Pollany, 2006, p. 6). The author describes the goalkeepers` performance as outstanding, pointing out in particular the goalkeepers` progress in 1-on-1 actions against free shots. something similar applies to the findings of a study where the authors compared statistical data on goalkeepers` performances acquired at three consecutive large handball competitions - ECh 2004, OG 2004 and WCh 2005 (Sevim, p. 69). Based on this comparison, the authors claimed that the goalkeepers` performances improved gradually. However, it should be considered that the national teams participating at the EChs are generally more equal in terms of their quality (European teams are higher in quality than those from other continents) compared to those participating at the WCh or even the OG. Considering the above, comparisons of such data and the conclusions based thereon could be misleading. It is only reasonable to compare data acquired at competitions of an equivalent or a similar level of quality. In the future, it would be reasonable to analyse differences in statistical data regarding the performance of goalkeepers playing for winning teams and those playing for losing teams. Some effort has already been made in this direction (Rogulj, 2000, p. 70; Gruiæ, 2006, p. 99). To add to the relevance of such analyses, the data should be processed in terms of the competition level at a championship (matches in the preliminaries separately from matches in the finals). This would allow us to gain in-depth knowledge of the goalkeepers` contributions to overall team performances.